2018
DOI: 10.1002/mus.26094
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of adipose‐derived stem cells in poloxamer hydrogel improves peripheral nerve regeneration

Abstract: Delivery of ASCs in poloxamer addresses multiple facets of the complexity of nerve/muscle unit regeneration, representing a promising avenue for further study. Muscle Nerve 58: 251-260, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 47 publications
3
47
0
Order By: Relevance
“…A common aspect of these reports is that better nerve regeneration is demonstrated through intervention, by introducing cells and devising structures for bridging, as compared with that in the nonintervention groups. However, in studies comparing results with autologous nerve grafting, reports have indicated that bridging with artificial material is difficult to compare with autologous nerve grafting 14–18,20 . In our study, axonal regeneration using a PGA‐c tube was further promoted by injecting dADSCs, but there was a significant difference in peripheral muscle innervation compared to that observed with autologous nerve grafting, as reported previously.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A common aspect of these reports is that better nerve regeneration is demonstrated through intervention, by introducing cells and devising structures for bridging, as compared with that in the nonintervention groups. However, in studies comparing results with autologous nerve grafting, reports have indicated that bridging with artificial material is difficult to compare with autologous nerve grafting 14–18,20 . In our study, axonal regeneration using a PGA‐c tube was further promoted by injecting dADSCs, but there was a significant difference in peripheral muscle innervation compared to that observed with autologous nerve grafting, as reported previously.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, axonal regeneration using a PGA‐c tube was further promoted by injecting dADSCs, but there was a significant difference in peripheral muscle innervation compared to that observed with autologous nerve grafting, as reported previously. There are a few reports evaluating nerve regeneration using a combination of tubulization and ADSCs in the critical gap model, 14,20 the results of which are comparable with our findings, even though our intervention procedure was simpler and easier to use in clinical applications. Peripheral nerve regeneration was clearly promoted by dADSCs in the critical nerve gap model, but it is not sufficient for clinical applications in terms of functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…As they describe in their article in this issue, Allbright et al . carried out a well‐constructed study investigating the potential of undifferentiated ADSCs (uADSC) delivered through poloxamer hydrogel to promote reinnervation in a rat sciatic nerve injury model.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that ADSCs can express nerve growth factors and can transform to a Schwann cell phenotype, resulting in greater axonal regeneration in animal models of peripheral nerve injury. [9][10][11][12] As they describe in their article in this issue, Allbright et al 13 carried out a well-constructed study investigating the potential of undifferentiated ADSCs (uADSC) delivered through poloxamer hydrogel to promote reinnervation in a rat sciatic nerve injury model. In addition to already being US Food and Drug Administration approved for clinical use, the poloxamer hydrogel has other useful attributes.…”
mentioning
confidence: 99%
See 1 more Smart Citation